School competition and efficiency in elementary schools in Mexico. (January 2016) - Garcia-Diaz, Rocio; del Castillo, Ernesto; Cabral, René
Abstract: This paper examines how competition impacts the technical efficiency of schools. We model competition between schools using Geographical Information System (GIS) tools in order to develop a Herfindahl–Hirschman market concentration index (HHI) and then follow a stochastic frontier analysis with alternative specifications that enable us to obtain the best unbiased efficient estimators. We find three important results. First, a higher degree of competition from public and private schools significantly increases elementary school efficiency in Mexico, as measured by the outcomes in a nationwide standardized test. Second, we find a positive, though small, association between expenditure on education and school outputs. Third, private schools perform significantly better due to the differential incentives they face in terms of competition.